2018
DOI: 10.1159/000490732
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Initial Thoracentesis for Malignant Pleural Effusion Stratified by Tumor Type in Patients with Strong Evidence of Metastatic Disease

Abstract: Background: Thoracentesis with cytological examination of pleural fluid is the initial test of choice for evaluation of pleural effusions in patients with suspected malignant pleural effusion (MPE). There is limited data on the sensitivity of thoracentesis stratified by tumor type. A better understanding of stratified sensitivities is of clinical interest, and may guide early and appropriate referral for pleural biopsy. Objective: The primary objective was sensitivity of thoracentesis with pleural fluid cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 25 publications
2
58
0
2
Order By: Relevance
“…The higher total yield of 73.2% of initial thoracentesis in our cohort, compared to the contemporary literature, is related to a high number of adenocarcinoma patients in this cohort. Similar results are reported by Grosu and colleagues (12). We have shown that such a difference in the thoracentesis yield with different tumor types persists even with subsequent thoracentesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher total yield of 73.2% of initial thoracentesis in our cohort, compared to the contemporary literature, is related to a high number of adenocarcinoma patients in this cohort. Similar results are reported by Grosu and colleagues (12). We have shown that such a difference in the thoracentesis yield with different tumor types persists even with subsequent thoracentesis.…”
Section: Discussionsupporting
confidence: 92%
“…After non-diagnostic thoracentesis, pleural biopsy is usually performed via medical pleuroscopy, video-assisted thoracoscopic surgery (VATS) or image guidance (10,11). There is limited literature on the diagnostic yield of cytology followed by pleural biopsy in patients with NSCLC related pleural effusions (12). In addition, the prognosis of patients with subtypes of NSCLC with pleural effusions has not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…The high morbidity of MPE continues to rise and therefore causes a heavy health care burden [ 28 ]. An ability to distinguish between MPE and BPE with considerable accuracy is clinically significant to avoid the deferred diagnosis of MPE [ [29] , [30] , [31] , [32] ]. Thus, this clinical study aiming to precisely differentiate MPE from BPE was of great public health implications.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications have looked at the risk of malignancy (ROM) for each of these categories. They have shown that values vary between affected cavities [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ]. Most studies, however, were published before the development and implementation of TIS, with few exceptions [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%